2015
DOI: 10.1007/s40820-015-0058-0
|View full text |Cite
|
Sign up to set email alerts
|

Single-Crystalline InGaAs Nanowires for Room-Temperature High-Performance Near-Infrared Photodetectors

Abstract: InGaAs is an important bandgap-variable ternary semiconductor which has wide applications in electronics and optoelectronics. In this work, single-crystal InGaAs nanowires were synthesized by a chemical vapor deposition method. Photoluminescence measurements indicate the InGaAs nanowires have strong light emission in near-infrared region. For the first time, photodetector based on as-grown InGaAs nanowires was also constructed. It shows good light response over a broad spectral range in infrared region with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
98
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(103 citation statements)
references
References 31 publications
5
98
0
Order By: Relevance
“…III-V semiconductor NWs with narrow bandgaps are considered as promising candidates for constructing IRPDs. To date, IRPDs based on InAs, InP, InGaAs, InPAs, and InGaSb nanowires have been reported [88,[94][95][96]. The fabrication of NW IRPDs can be categorized into three types, namely, photoconductor, phototransistor (where photosensitivity is greatly enhanced by an additional gate bias), and heterostructure NW devices including homo-/heterojunction and Schottky photodiodes.…”
Section: Nanowires and Nanopillar For Irpdmentioning
confidence: 99%
“…III-V semiconductor NWs with narrow bandgaps are considered as promising candidates for constructing IRPDs. To date, IRPDs based on InAs, InP, InGaAs, InPAs, and InGaSb nanowires have been reported [88,[94][95][96]. The fabrication of NW IRPDs can be categorized into three types, namely, photoconductor, phototransistor (where photosensitivity is greatly enhanced by an additional gate bias), and heterostructure NW devices including homo-/heterojunction and Schottky photodiodes.…”
Section: Nanowires and Nanopillar For Irpdmentioning
confidence: 99%
“…Pan and co‐workers realized the asymmetric light propagation in composition‐graded semiconductor NWs, which made them attractive candidates for integrated nanophotonic applications . In addition to the superior optical properties of NWs, the high performance electronic and optoelectronic devices were also obtained due to the confined carrier transport in 1D channel and high specific surface area of the NW . Vertical InAs NW wrap gate transistors were obtained with a unity current gain cutoff frequency >7 GHz and maximum oscillation frequency >20 GHz .…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al . () demonstrated that the apparent elemental distribution in InGaAs nanowires using energy‐dispersive X‐ray spectroscopy (EDXS) elemental mapping is strongly dependent on sample geometry so they could not quantify the In distribution fully. Johannes et al .…”
Section: Introductionmentioning
confidence: 99%
“…Several groups used quantification of the In concentration of InGaN quantum wells in GaN nanowires by using the Cliff-Lorimer method (Zhang et al, 2016;Bonef et al, 2017). Tan et al (2016) demonstrated that the apparent elemental distribution in InGaAs nanowires using energy-dispersive X-ray spectroscopy (EDXS) elemental mapping is strongly dependent on sample geometry so they could not quantify the In distribution fully. Johannes et al (2017) evaluated the composition of GaAs embedded in a silicon nanowire by using energy dispersive X-ray fluorescence, neglecting X-ray absorption effect in a ß190 nm thick nanowire where the absorption of soft X-ray lines (Ga L or As L) should not be neglected.…”
Section: Introductionmentioning
confidence: 99%